2021
DOI: 10.1093/rheumatology/keab345
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster following BNT162b2 mRNA COVID-19 vaccination in patients with autoimmune inflammatory rheumatic diseases: a case series

Abstract: Objectives As global vaccination campaigns against COVID-19 disease commence, vaccine safety needs to be closely assessed. The safety profile of mRNA-based vaccines in patients with autoimmune inflammatory rheumatic diseases (AIIRD) is unknown. The objective of this report is to raise awareness to reactivation of herpes zoster (HZ) following the BNT162b2 mRNA vaccination in patients with AIIRD. Methods The safety of the BNT16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
164
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(180 citation statements)
references
References 22 publications
2
164
1
3
Order By: Relevance
“…The past months have witnessed the first large-scale application of mRNA vaccines in the human world. Concerns still exist since the occasional reports of severe or concerning AEs like anaphylaxis (6, 7), virus infection in patients with immune diseases (8), facial nerve palsy (9, 10), and even death (9). As a complement to clinical trials, real-world AE monitoring is crucial to expand our understandings of suspected AEs following immunization (AEFIs).…”
mentioning
confidence: 99%
“…The past months have witnessed the first large-scale application of mRNA vaccines in the human world. Concerns still exist since the occasional reports of severe or concerning AEs like anaphylaxis (6, 7), virus infection in patients with immune diseases (8), facial nerve palsy (9, 10), and even death (9). As a complement to clinical trials, real-world AE monitoring is crucial to expand our understandings of suspected AEs following immunization (AEFIs).…”
mentioning
confidence: 99%
“…Recently, two cases of Herpes Zoster reactivation have been associated with COVID-19 vaccination; the first, a 78-year-old man with a history of hypertension, cerebrovascular accident and bladder cancer, after the inoculation of an inactivated COVID-19 vaccine [ 4 ]; the second, a 79-year-old man with a history of hypertension and anti-neutrophilic cytoplasmic antibody-related glomerulonephritis, after mRNA COVID-19 vaccination [ 5 ]. Moreover, Furer and colleagues recently described an interesting case series of varicella–zoster virus reactivation in 6 patients affected by autoimmune inflammatory rheumatic disease after Pfizer-BioNTech inoculation [ 6 ]. Thus, the present report constitutes the first case documented on a rare case of varicella–zoster virus reactivation on a healthy, young adult male without pre-existing conditions.…”
Section: Varicella–zoster Virus Reactivation After Bnt162b2 Vaccine Second Dosementioning
confidence: 99%
“…Here, we describe a case of itchy papulovesicular rash, which is consistent with shingles reactivation following Pfizer-BioNTech vaccine second dose. Cases of varicella–zoster virus reactivation due to COVID-19 and its vaccination have already been reported in older individuals with pre-existing conditions, including hypertension, cerebrovascular accident and bladder cancer, with hypertension and anti-neutrophilic cytoplasmic antibody-related glomerulonephritis, or with autoimmune inflammatory rheumatic disease [ 2 6 ]. This report is the first to describe a case of shingles reactivation on a healthy, young adult male in absence of pre-existing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Both Eid et al 3 and Bostan and Yalici-Armagan 4 observed cutaneous herpes zoster reactions after COVID-19 vaccination in male patients in their 70s. Recently, Furer et al 5 published a case series of patients with autoimmune inflammatory rheumatic diseases who presented with reactivation of herpes zoster virus after COVID-19 vaccination. We concur with Rodr ıguez-Jim enez et al 1 that the association of cases with herpes zoster after the COVID-19 vaccination is inconclusive and potentially coincidental, but we would like to add to the literature a report of a similar case in a patient that presented to our dermatology clinic.…”
mentioning
confidence: 99%